Enhancing the Antibiofilm Activity of β-1,3-Glucanase-Functionalized Nanoparticles Loaded With Amphotericin B Against Candida albicans Biofilm - Tan, Yulong; Ma, Su; Ding, Ting; Ludwig, Roland; Lee, Jintae; Xu, Jiaman (Frontiers in Microbiology, 2022)
Candida biofilm-related infections cause increased morbidity and mortality in patients with a reduced immune response. Traditional antifungal therapies have proven to be insufficient as the biofilm matrix acts as a perfusion barrier. Thus, novel methods are required to improve drug delivery and kill Candida within the biofilm. In this study, chitosan nanoparticles (CSNPs) loaded with Amphotericin B (AMB), which were functionalized with β-1,3-glucanase (Gls), were fabricated (CSNPs-AMB-Gls), and their antibiofilm activity against Candida albicans biofilm was evaluated in vitro. Scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM) were employed to examine biofilm architecture and cell viability. CSNPs-AMB-Gls inhibited planktonic cell growth and biofilm formation effectively and exhibited the highest efficacy on the removal of a mature biofilm than free AMB or CSNPs-AMB. The created nanoparticles (NPs) were found to penetrate the biofilm so as to directly interfere with the cells inside and disassemble the biofilm matrix. CSNPs-AMB-Gls could also eradicate biofilms from clinical isolates. These results suggest the potential applicability of CSNPs-AMB-Gls for the treatment of Candida biofilm-related infections.